To go or not to go : assessing the “Borga” image as a factor in the decision-making process of the prospective Ghanaian migrant - Nyarko-Afriyie, Daniel (2019)
Ghana plays an active role in international migration by contributing significant numbers to the pool of migrants from Sub-Saharan African invading European shores legally and illegally. By and large, many more Ghanaians are desirous of leaving the country to seek greener pastures elsewhere. This research, therefore, examines the representation of the Borga in the Ghanaian context and the role it plays in the prospective migrant’s decision to either move abroad or stay at home in Ghana. The Borga is a folk term used to describe returned migrants and people with international travelling experience. Using the qualitative research method, the data of this thesis consists of audio recorded and transcribed interviews of 28 prospective Ghanaian migrants. Relying on the cumulative causation theory as its main theoretical framework, the research data has been analyzed and interpreted using the thematic content analysis approach. The results of this thesis show that by constantly being represented in a positive light, the image of the Borga serves as an additional impetus to the desires of the prospective migrant to move abroad too. Additionally, it emerged that the persistence of the positive representation of the Borga image serves as evidence to the social beliefs around migration and provides positive values that make the cost-benefit calculations of the prospective migrant yield positive results. The study concludes that the Borga image is an important stimulus for Ghana’s international out-migration.